The effect of virgin coconut oil loaded solid lipid particles (VCO-SLPs) on skin hydration and skin elasticity - Mohamed Noor, Norhayati (Penerbit UTM Press, 2013)
Virgin Coconut Oil is usually extracted from well matured and fresh coconut through specialized processes without damaging its natural nutrition. In this work, formulation, characterization and efficacy of VCO-SLPs have been studied. VCO-SLPs were prepared using ultrasonification of molten stearic acid and virgin coconut oil in an aqueous solution and particles with the size of 0.608 μm have been obtained. 20% concentration of VCO-SLPs of 0.608 μm particle size was added into the base lotion. Sensory study and skin evaluation study was conducted to compare the difference between lotion containing VCO-SLPs and lotion without VCO-SLPs. Moisturizing lotion incorporated with VCO-SLPs was found to increase skin hydration and skin elasticity by 24.8% and 2.60% respectively from day 0 to day 28. This shows that solid lipid particles has the potential to be utilized as a carrier for improved dermal delivery of VCO.